Global Strategy for the Diagnosis, Management, and Prevention of Chronic Obstructive Lung Disease: the GOLD science committee report 2019. Issue 5 (18th May 2019) - Singh, Dave; Agusti, Alvar; Anzueto, Antonio; Barnes, Peter J.; Bourbeau, Jean; Celli, Bartolome R.; Criner, Gerard J.; Frith, Peter; Halpin, David M.G.; Han, Meilan; López Varela, M. Victorina; Martinez, Fernando; et al.
Precision medicine is a patient-specific approach that integrates all relevant clinical, genetic and biological information in order to optimise the therapeutic benefit relative to the possibility of side-effects for each individual. Recent clinical trials have shown that higher blood eosinophil counts are associated with a greater efficacy of inhaled corticosteroids (ICSs) in chronic obstructive pulmonary disease (COPD) patients. Blood eosinophil counts are a biomarker with potential to be used in clinical practice, to help target ICS treatment with more precision in COPD patients with a history of exacerbations despite appropriate bronchodilator treatment. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 pharmacological treatment algorithms, based on the ABCD assessment, can be applied relatively easily to treatment-naive individuals at initial presentation. However, their use is more problematic during follow-up in patients who are already on maintenance treatment. There is a need for a different system to guide COPD pharmacological management during follow-up. Recent large randomised controlled trials have provided important new information concerning the therapeutic effects of ICSs and long-acting bronchodilators on exacerbations. The new evidence regarding blood eosinophils and inhaled treatments, and the need to distinguish between initial and follow-up pharmacological management, led to changes in the GOLD pharmacological treatment recommendations. This article explains the evidence and rationale for the GOLD 2019 pharmacological treatment recommendations. The GOLD 2019 report has new pharmacological treatment recommendations, based on recent evidence from clinical trials. Blood eosinophils are recommended as a biomarker to support clinical decisions regarding the use of inhaled corticosteroids. http://ow.ly/oerU30nSKUX